A Note About Parabolic Systems and Analytic Semigroups (Journal of Partial Differential Equations, 2011)
We investigate the question whether certain parabolic systems in the sense of Petrovskii fulfill the resolvent estimate required for the generation of an analytic semigroup and apply the result to a problem concerning the diffusion of gases.
Keywords: Parabolic systems; cross diffusion; analytic semigroups